THE KNOWLEDGE ON LYME BORRELIOSIS AND OTHER TICK-BORNE DISEASES AMONG NURSING STUDENTS FROM POLAND AND SLOVAKIA - Pańczuk, Anna; Tokarska-Rodak, Małgorzata; Mikuľáková, Wioletta; Kendrová, Lucia; Magurová, Dagmar; Wasilewska, Małgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Tick-borne diseases are infectious diseases transmitted by the bites of infected ticks. The most common vector-borne disease in Europe is Lyme borreliosis (LB). The number of the reported cases of LB has been steadily increasing. For this reason, it is important to undertake educational activities in the field of tick-borne diseases. The aim of the study was to investigate the level and scope of knowledge on tick-borne diseases among nursing students from Poland and Slovakia. The study sample consisted of 428 nursing students (192 students of the State School of Higher Education in Biała Podlaska, Poland and 236 students of the University in Presov, Slovakia). The knowledge of the surveyed students on tick-borne diseases is limited. Polish students demonstrated greater knowledge about LB, while students from Slovakia showed greater awareness of the threat posed by tick-borne encephalitis. Particularly worrying is the lack of knowledge on proper way of removal of a tick attached to the skin. Students recognize the need to broaden their knowledge on tick-borne diseases, which should be taken into consideration in realized studies curricula.